The Effect of Nursing Internships on the Effectiveness of Implementing Information Technology Teaching - Tseng, Li-Ping; Hou, Tung-Hsu; Huang, Li-Ping; Ou, Yang-Kun (Frontiers in Public Health, 2022)
In nursing education, the diversity of clinical scenarios is complex and dynamic, and it is a chal-lenge for nursing students to learn this clinical knowledge in conventional teaching mechanisms. However, integrating information technology into teaching can promote diversity of learning en-vironment. This study aimed to investigate the effectiveness of teaching mechanisms which com-bined clinical simulation scenario and Information Technology Integrated Instruction. This study applied innovative experimental teaching in medical–surgical and critical care nursing courses for nursing students in their fourth or fifth year at a five-year junior college. Instructional systems design was combined with clinical simulation scenarios and technology to develop multidimen-sional teaching strategies. Fifth-year students’ overall OSCE mean score was considerably higher than that of fourth-year students; specifically, their scores on basic life support and care for sub-dural hemorrhage varied substantially. Compared with fourth-year students, fifth-year students performed considerably greater on situational awareness. The results of the present study can be used to develop nursing core competencies and improve the clinical care competency of nursing personnel.